If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4log(x) + -6 = 2log(x) Multiply glo * x 4glox + -6 = 2log(x) Reorder the terms: -6 + 4glox = 2log(x) Multiply glo * x -6 + 4glox = 2glox Solving -6 + 4glox = 2glox Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-2glox' to each side of the equation. -6 + 4glox + -2glox = 2glox + -2glox Combine like terms: 4glox + -2glox = 2glox -6 + 2glox = 2glox + -2glox Combine like terms: 2glox + -2glox = 0 -6 + 2glox = 0 Add '6' to each side of the equation. -6 + 6 + 2glox = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 2glox = 0 + 6 2glox = 0 + 6 Combine like terms: 0 + 6 = 6 2glox = 6 Divide each side by '2lox'. g = 3l-1o-1x-1 Simplifying g = 3l-1o-1x-1
| 23=5(x+3) | | 4lg(x)-6=2lg(x) | | gx=144 | | (x+1)(x-2)=(x-1)(x-1) | | -5/6=3/4n | | (3x-1)/(x-4)=0 | | 5x-8=3x-11+8 | | 2z-12-1=z-25+z | | 3/1728 | | 6(-2-3x)+8= | | -x-4=3x+6 | | -3-3x/21 | | 2(3m-9)-3(m-2)= | | 4x+5=8x+5 | | 7x-2=9x-4 | | 9x-9=19x-19 | | 11x-12=13x-20 | | 6x+3y=153 | | x+y=1.23 | | 5-x=32 | | 2x+15=13x+1 | | 10x+(12-x)=9x+12 | | 5x-1=10x-17 | | 19x+2=3x+14 | | 10/x=6.3681 | | 4.6/y=44.16 | | -32*Y=-22336 | | 10y+15x=5 | | (12-x)+x=12+36 | | (12-x)+x=12 | | 143=6x+17 | | 5(2y+4)=24 |